Relevance of Records Management in Delivery of Health Services in Health Centers: A Case Study Kabale Regional Referral Hospital. - Tumusiime, Irene (Kabale University, 2024)
The research study was about the role played by records management in the delivery of services in hospitals and was carried out at Kabale Regional Referral Hospital. The objectives of the study were; to identify the kinds of records created and kept at the Hospital, to find out the filing systems and storage types of equipment used at the hospital, to establish the challenges faced in managing records at the hospital, and to suggest possible solutions to the problems. Data was collected from 8 respondents under the guidance of questionnaires, observations, and interviews. The study revealed that the kinds of records created and kept include; Patient records, financial records, and, administrative records. The filing systems used at the hospital are Alphabetic, Numerical, and Chronological filling systems. The storage types of equipment used are open shelves, computers, boxes, cupboards, file folders, and file cabinets. The challenges faced in managing the records include; limited space, misfiling, staff shortage, insufficient storage equipment, and poor folder materials. Solutions include the use of passwords, ant viruses, using box files, job training, and preservation and conservation.